Facile photohydroxylation of ZnS nanobelts for enhanced photocatalytic activity. Issue 1 (February 2018) - Ham, Sooho; Jang, Du-Jeon
Graphical abstract: Highlights: ZnS nanobelts have been hydroxylated with hydrogen peroxide under UV irradiation. Facile photohydroxlation has enhanced the photocatalytic activity of ZnS nanobelts. Surface OH groups and surface defects block the recombination of excited charges. Surface-adsorbed hydroxyl groups enhance the generation of hydroxyl radicals highly. The efficient generation of hydroxyl radicals enhances photocatalytic activity. Abstract: The photocatalytic performances of ZnS photocatalysts have been extensively enhanced by treating ZnS nanobelts for 10 min with hydrogen peroxide under Xe-lamp irradiation. The photocatalytic degradation reaction of 4-nitrophenol via photohydroxylated ZnS nanobelts takes place faster six times than that via pristine ZnS nanobelts, demonstrating that the simple and facile photohydroxylation process increases the photocatalytic activity of ZnS nanobelts extensively. Photoluminescence spectra and kinetic profiles have suggested that surface hydroxyl groups as well as surface defects increase the separation rate of photogenerated charges, enhancing the photocatalytic activity of 4-nitrophenol degradation. Radical species tests have indicated that the photocatalytic performance of ZnS nanobelts is mainly contributed by hydroxyl radicals generated by the photooxidation of surface-adsorbed hydroxyl groups. Because hydroxyl groups are adsorbed on the surfaces of photocatalysts, diffusion is not necessary when hydroxyl radicals are formed by photoexcited holes. Thus, the photocatalytic degradation of 4-nitrophenol via ZnS nanobelts follows the zero-order kinetics. The generation of hydroxyl radicals is promoted by the retarded recombination of photoexcited charges, leading to the enhancement of the photocatalytic activity of ZnS nanobelts. Overall, a simple and facile photohydroxylation process increases the photocatalytic performances of ZnS photocatalytsts enormously via forming reactive hydroxyl radicals, which are readily generated by the photooxidation of surface-adsorbed hydroxyl groups. Overall, our facile and eco-friendly photohydroxylation method is suggested to have great potential for industrial applications.